2021
DOI: 10.1186/s12864-021-07746-4
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark of 16S rRNA gene amplicon sequencing using Japanese gut microbiome data from the V1–V2 and V3–V4 primer sets

Abstract: Background 16S rRNA gene amplicon sequencing (16S analysis) is widely used to analyze microbiota with next-generation sequencing technologies. Here, we compared fecal 16S analysis data from 192 Japanese volunteers using the modified V1–V2 (V12) and the standard V3–V4 primer (V34) sets to optimize the gut microbiota analysis protocol. Results QIIME1 and QIIME2 analysis revealed a higher number of unclassified representative sequences in the V34 data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 47 publications
3
47
0
Order By: Relevance
“…Many studies have compared the performance of different sets of 16S rRNA primers for microbiota profiling in different environments (10)(11)(12)(13). These studies consistently demonstrated that the choice of the 16S rRNA primer set can significantly influence the analysis of microbiota diversity and composition.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many studies have compared the performance of different sets of 16S rRNA primers for microbiota profiling in different environments (10)(11)(12)(13). These studies consistently demonstrated that the choice of the 16S rRNA primer set can significantly influence the analysis of microbiota diversity and composition.…”
Section: Discussionmentioning
confidence: 97%
“…Although all nine hypervariable regions are taxonomically informative, the amount and quality of information retrieved varies per region according to the studied environment. For instance, Fadeev et al (2021) showed that V4V5 is superior to V3V4 for microbiota profiling of environmental arctic samples (10), and Kameoka et al (2021) found that V1V2 is more precise than V3V4 for gut microbiota profiling of Japanese individuals (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extraction from the fecal samples was performed using an automated DNA extraction system (GENEPREP STAR PI-480, Kurabo Industries Ltd., Osaka, Japan) according to the manufacturer’s protocols. The V1–V2 region of the 16S rRNA gene was amplified using a forward primer (16S_27Fmod: TCG TCG GCA GCG TCA GAT GTG TAT AAG AGA CAG AGR GTT TGA TYM TGG CTC AG) and a reverse primer (16S_338R: GTC TCG TGG GCT CGG AGA TGT GTA TAA GAG ACA GTG CTG CCT CCC GTA GGA GT) and KAPA HiFi HotStart ReadyMix (Roche, Basel, CHE) according to a previous study [ 13 ]. To sequence 16S amplicons using the Illumina MiSeq platform, dual index adapters were attached using the Nextera XT Index Kit.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we selected the V3-V4 region in consideration of the longest read length and cost, but there is a limitation in not investigating the difference in results that may occur when other regions are targeted. In Partial 16s rRNA gene sequencing, the difference in results pertaining to the selection of hypervariable regions of the 16S rRNA gene on various clinical samples has been previously reported [44,45]. For respiratory samples, the V1-V2 region was selected for better species-level taxonomic assignment in a study with endotracheal aspirates and oropharyngeal swab [40].…”
Section: Plos Onementioning
confidence: 99%